Microinjection of follicle-enclosed mouse oocytes - Jaffe, Laurinda A. (2009)
The mammalian oocyte develops within a complex of somatic cells known as a follicle, within which signals from the somatic cells regulate the oocyte, and signals from the oocyte regulate the somatic cells. Because isolation of the oocyte from the follicle disrupts these communication pathways, oocyte physiology is best studied within an intact follicle. Here we describe methods for quantitative microinjection of follicle-enclosed mouse oocytes, thus allowing the introduction of signaling molecules as well as optical probes into the oocyte within its physiological environment.